Pemanfaatan Media Kantong Bilangan dalam Pembelajaran untuk Meningkatkan Pemahaman Operasi Hitung Siswa Kelas III di SDN Sebaung 2 - Dzaky Isyuniandri; Alfiatus Syarofah (Dinamika Sosial : Jurnal Pengabdian Masyarakat dan Transformasi Kesejahteraan, 2025)
This community service activity was conducted at SDN Sebaung 2 with the aim of improving third-grade students’ understanding of arithmetic operations through the use of "number pocket" media. The main issue identified was the low comprehension of addition and subtraction operations, caused by monotonous teaching methods that did not actively engage students. The activity began with classroom observation and interviews with the teacher, followed by designing a solution using number pocket media, preparing materials, implementing the learning session, and conducting a brief evaluation. The methods used included demonstration and a learning-by-playing approach to create an enjoyable and interactive learning environment. The results showed that students found it easier to understand the material, were more active during the learning process, and demonstrated high enthusiasm. The number pocket media proved to be effective in supporting the learning process and can serve as an alternative method for teachers to deliver arithmetic material in a more engaging way.